2014
DOI: 10.18632/oncotarget.2531
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the viability of Nf1 deficient cells by PKC isoforms

Abstract: Suppression of protein kinase C (PKC) is known to be synthetically lethal with ras mutations in various types of cancer cells. The studies also showed that blockade of PKC affected the viability of Nf1 deficient cells. Since PKC family consists of more than 10 isoforms, our study aimed at identifying which isoform(s) played the crucial role in sensitizing Nf1 deficient cells to apoptosis. Using genetic and chemical PKC inhibitors, we demonstrated that the concurrent inhibition of PKC α and β induced Nf1 defici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…The inhibition of PKC triggered apoptosis in cultured cells expressing v-ras or cancer cells harboring mutated ras [ 13 17 ]. However, the underlying mechanisms by which oncogenic ras induces apoptosis remain unclear.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The inhibition of PKC triggered apoptosis in cultured cells expressing v-ras or cancer cells harboring mutated ras [ 13 17 ]. However, the underlying mechanisms by which oncogenic ras induces apoptosis remain unclear.…”
Section: Resultsmentioning
confidence: 99%
“…The increased amount of the GTP-bound Ras was detected in all cells expressing aberrant K-ras , in comparison that only the baseline level of active Ras was revealed by the antibody in HPNE cells. Our previous reports demonstrated that murine fibroblasts ectopically expressing mutant ras were susceptible to apoptosis after the co-suppression of PKC α and β isoforms [ 13 17 ]. Therefore, the susceptibility of the pancreatic cancer cells to the co-inhibition of PKC α/β was studied.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations